Effectiveness of infection control measures informed by a modified Blue-Carba test in reducing rectal carriage of carbapenemase-producing bacteria in general wards: a prospective interrupted time series study - Castro, Maximiliano Gabriel; Argarañá, Fernanda; Bernasconi, Carla; Margenet, Leticia; Amato, Ana Paula; Coduri Anthonioz Blanc, Joaquín Ignacio; Rottoli, Erwin Alexander; Protto, Manuel; Vicino, Macarena; Sadonio, María José; Galluccio, Federico Rafael; Musacchio, Héctor Mario; et al. (Frontiers in Pharmacology, 2025)
IntroductionThe spread of carbapenemase-producing bacteria (CPB) is exacerbated in hospital settings, making the surveillance of rectal carriage of CPB crucial to halt their spread. However, the processing time until detection with traditional methods and the cost of new techniques limit their implementation. We aimed to evaluate the effectiveness of infection prevention and control (IPC) measures guided by a novel algorithm (NA) for rectal swab processing, which incorporated a modified Blue-Carba test (mBCT), in reducing carbapenemase-producing bacteria (CPB) rectal carriage prevalence in general wards of a tertiary-care hospital from Argentina. Additionally, we assessed the impact of this algorithm on microbiological turnaround time (mTAT) and time to positive results (TPR).Materials and methodsAn experimental and quasi-experimental designs were combined into a prospective interrupted time series study structured in three phases: P1 (February 2022-July 2022), P2 (August 2022-January 2023; intervention) and P3 (February 2023-July 2023). Briefly, the NA included as key steps a 6-hour pre-incubation at 37 °C in nutrient broth, followed by a 15-minute centrifugation at 3,200 rpm. The mBCT was set at pH 10.7 using 9 mg of imipenem in a final volume of 150 μL and was validated against conventional methods testing 1,120 samples. It was subsequently implemented to assess its impact on hospital CPB prevalence and the effectiveness of IPC measures. Patients were randomly selected for CPB rectal screening during Phases 1 and 3 and provided informed consent for inclusion.ResultsThe mBCT significantly shortened the mTAT and TPR compared to standard approaches (<24 h vs. 4d, p < 0.001), showing moderate sensitivity [54.6% (IC95% 45.2–63.7)] and high specificity [99.8% (IC 95% 99.3–100)]. The IPC intervention guided by the mBCT reduced CPB prevalence in general wards (8.1% vs. 13.8%, p = 0.006).ConclusionThe implementation of the NA reduced mTAT with high sensitivity, while the mBCT also contributed to reducing TPR with high specificity. Integrating the NA and mBCT into IPC protocols led to a decrease in CPB rectal carriage prevalence in general wards, underscoring their diagnostic, epidemiological and thus IPC benefits.